KEKUATAN PUTUSAN HAKIM TERHADAP SENGKETA PERJANJIAN ARBITRASE (Studi Kasus Televisi Pendidikan Indonesia Vs Hari Tanoe) - Wika Yudha Shanty (University of Merdeka Malang, 2015)
The consequences of arbitrary verdict has to put by good intention from both sides who have chosen to resolutetheir dispute outside the court. It is weird if both sides who chose resolute their dispute to the arbitraryinstitution end up complaining about the institution authority. In other words recognition and effectivity ofarbitrary verdict is relied on both sides who chose arbitrary institution. The contradiction between courtverdict and arbitrary verdict rises a new question about legality of court verdict put by judges, meanwhile thecontract has arbitrary clause which accepted by both sides. The goal and focus of this research is rely on howlegality of arbitrary verdict if in the contract has arbitrary clause to resolute dispute or different opinionbetween them. Achievement indicator of this research is explanation based law regulation if there is arbitraryclause and effect of the verdict if court and arbitrary institution put verdict to the same case.